2017
DOI: 10.2147/ijn.s140605
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-mediated synthesis of graphene oxide–silver nanoparticle nanocomposites: a suitable alternative nanotherapy for neuroblastoma

Abstract: Background Graphene and graphene-related materials have gained substantial interest from both academia and industry for the development of unique nanomaterials for biomedical applications. Graphene oxide (GO) and silver nanoparticles (AgNPs) are a valuable platform for the development of nanocomposites, permitting the combination of nanomaterials with different physical and chemical properties to generate novel materials with improved and effective functionalities in a single platform. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 111 publications
6
53
3
Order By: Relevance
“…These results indicate that high concentrations of AgNPs damage cellular membrane integrity. Our results agree with those of previous reports showing that AgNPs induce leakage of LDH in different type of cancer cells and non-cancer cells, including human breast cancer cells [14,38], human lung cancer cells [17], human ovarian cancer cells [16], human neuroblastoma cells [39], human microvascular endothelial cells [42], male somatic cells, spermatogonial stem cells [8], and neural stem cells [43]. Collectively, the results suggest that reduced viability was observed in HCT116 cells exposed to AgNPs, which correlates with the increased leakage of LDH and significantly strong cytotoxicity.…”
Section: Resultssupporting
confidence: 93%
“…These results indicate that high concentrations of AgNPs damage cellular membrane integrity. Our results agree with those of previous reports showing that AgNPs induce leakage of LDH in different type of cancer cells and non-cancer cells, including human breast cancer cells [14,38], human lung cancer cells [17], human ovarian cancer cells [16], human neuroblastoma cells [39], human microvascular endothelial cells [42], male somatic cells, spermatogonial stem cells [8], and neural stem cells [43]. Collectively, the results suggest that reduced viability was observed in HCT116 cells exposed to AgNPs, which correlates with the increased leakage of LDH and significantly strong cytotoxicity.…”
Section: Resultssupporting
confidence: 93%
“…Compared to pristine AgNPs, GO-AgNPs signi cantly induced generation of ROS in the macrophage in a dose-dependent manner [48]. In current study, the level of ROS increased signi cantly at a 1.4-and 1.8-fold in caprine fetal broblast cells after treatment with 4 and 8 µg/mL GO-AgNPs for 24 h. Our results are consistent with previous reports on various cancer cell lines with graphene and graphenerelated materials [30,42]. The up-regulated ROS level in caprine fetal broblast cells alters the mitochondrial functions and plays a key role in apoptosis induction, which proved by the data of Annexin V/PI double labeling assay and increasing level of caspase-3.…”
Section: Discussionsupporting
confidence: 91%
“…The present data showed that 20 nm GO-AgNPs reduced cell growth, viability and induced morphological changes in a concentration-dependent manner. In our previous study, GO-AgNPs signi cantly decreased the human ovarian cancer cell viability with an IC 50 of 5 µg/mL [42], which is lower than that in the present study, suggesting that caprine fetal broblast cells are less sensitive to GO-AgNPs than human cancer or mouse cells. AgNPs with different sizes and surface coatings or without coatings are likely to contribute to these different results.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations